FAKTOR RESIKO TERJADINYA LGBT PADA ANAK DAN REMAJA - Zusy Aryanti (Postgraduate State Islamic Institute (IAIN) Metro, 2016)
The increasing of LGBT in Indonesia which the followers do the activities as their identity. The strong ignorance as the LGBT’s that awarely declare the legality of their exixtences to the goverment. In turn, the movement of LGBT shows the problems in scholars who disagree with the LGBT. LGBT is thought as soul stress and it can be cured. The current paper describes the factors which are particularly impacted the LGBT activists. The environment may be impacted the behaviours and those can be impacted by the environment, thus when the internalization of the value happens, the human can limit theirself to receive politely about LGBT. The individuall cab change the perception and paradigm to reject or receive the phenomenon.